#### Question

Verify whether the following zeroes of the polynomial, indicated against them.

p(x) = (x + 1) (x – 2), x = – 1, 2

#### Solution

If *x* = −1 and *x* = 2 are zeroes of polynomial *p*(*x*) = (*x* +1) (*x* − 2), then *p*(−1) and *p*(2)should be 0.

Here, *p*(−1) = (− 1 + 1) (− 1 − 2) = 0 (−3) = 0, and

* p*(2) = (2 + 1) (2 − 2 ) = 3 (0) = 0

Therefore, *x* = −1 and *x *= 2 are zeroes of the given polynomial.

Is there an error in this question or solution?

Solution Verify whether the following zeroes of the polynomial, indicated against them. p(x) = (x + 1) (x – 2), x = – 1, 2 Concept: Zeroes of a Polynomial.